2016
DOI: 10.18805/lr.v0i0.7588
|View full text |Cite
|
Sign up to set email alerts
|

Investigating morpho-physiological traits and agro-meteorological indices in green gram [Vigna radiata L. Wilczek] for terminal heat tolerance

Abstract: Forty genotypes of greengram were studied to ascertain the genetic variability and trait association among some important morpho-physiological traits and agro-meterological indices under heat stress condition. The results indicated that both GCV and PCV estimates were high for photo thermal index, heat use efficiency and seed yield. High heritability coupled with moderate genetic advance as per cent of mean was recorded for photo-thermal unit and relative temperature depression indicated that involvement of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…A wide range of variation was observed among the different stress indices for all 48 genotypes of fenugreek and Kumar et al (2020) in mungbean also found the same findings. To evaluate drought tolerant genotypes using TOL index, higher value of TOL demonstrates more changes of genotype yield in stress and non-stress conditions and shows the susceptibility to non-stress condition.…”
Section: Mean Comparisonsupporting
confidence: 70%
“…A wide range of variation was observed among the different stress indices for all 48 genotypes of fenugreek and Kumar et al (2020) in mungbean also found the same findings. To evaluate drought tolerant genotypes using TOL index, higher value of TOL demonstrates more changes of genotype yield in stress and non-stress conditions and shows the susceptibility to non-stress condition.…”
Section: Mean Comparisonsupporting
confidence: 70%
“…Most of the Vigna crops are very frequently subjected to extreme environmental conditions that are many times at the upper extremes as far as temperature is concerned. However, a very limited study has been conducted till present on the aspect of high-temperature tolerance in mung bean ( Kumar et al, 2016 , 2017 ). The linkage of high-throughput phenotyping platforms for the screening of target traits with omics interventions can give a clue for its mitigation ( Pratap et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also improves soil health by fixing the atmospheric nitrogen into the soil through symbiosis with Rhizobium [ 4 , 5 ], which enhances the yield of the subsequent crop. Despite being of economic importance, the productivity is still low due to erratic climatic conditions [ 6 , 7 , 8 , 9 , 10 ] and various biotic stresses [ 11 , 12 , 13 , 14 , 15 ]. Insect pests are the major production constraints to pulses; among them, the pulse beetle poses a serious threat to stored grains.…”
Section: Introductionmentioning
confidence: 99%